Plan de negocios para la creación de una empresa dedicada a la producción y exportación de piña rellena de palmito en salsa de sandía con acompañamiento de queso mozarella - Chávez García, Elsita Margoth (2012)
For its geographic and climatic conditions, Ecuador posses ideal characteristic for agricultural development. This factor, along with technological advances and labor support, has permitted the industrialization of diverse products. The present business plan consists with the creation of a business for the production and exportation of a pineapple filled with palm heart in watermelon sauce, accompanied with mozzarella cheese. The objective is to give value to national raw material, applying necessary studies to reach international markets with a production that complies with high standards of quality and hygiene. The principal advantage is to try a new product, with ingredients that are well known overseas, which is attractive to the costumer. Through the environmental analysis, it was determined that the industry in which the product was developed has shown a sustainable growth in the last few years (7.33%); increasing its exportations in volume and value. The company will be constituted as a limited company with three partners. The market intelligence reflects the United States of America as an attractive market for exportation, and France and Belgium as alternative markets. The United States was chosen, was ranked fifth in the worlds ranking competitiveness with a GDP of 47184 USD. The strategy that will be used to enter the market is selective distribution. In the operation plan a production process was established and the capacity production was defined through strategy processes, localization, and provisioning. The Management team and the necessary human resources (three administrative workers and four in production) were determined.